2021
DOI: 10.1038/s43705-021-00079-z
|View full text |Cite
|
Sign up to set email alerts
|

Microvolume DNA extraction methods for microscale amplicon and metagenomic studies

Abstract: Investigating the composition and metabolic capacity of aquatic microbial assemblages usually requires the filtration of multi-litre samples, which are up to 1 million-fold larger than the microenvironments within which microbes are predicted to be spatially organised. To determine if community profiles can be reliably generated from microlitre volumes, we sampled seawater at a coastal and an oceanic site, filtered and homogenised them, and extracted DNA from bulk samples (2 L) and microvolumes (100, 10 and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…When compared to the concurrent Niskin bottle samples, the sampler captured a near-identical community for both bacteria and phytoplankton at all stations. This is despite differences in the protocol such as volume filtered and temporal resolution, aligning with prior studies, which have shown similar results 42,43 . A recent study performed using the 3G ESP also demonstrated that results were equivalent between autonomous and manual sampling 44 .…”
Section: Discussionsupporting
confidence: 89%
“…When compared to the concurrent Niskin bottle samples, the sampler captured a near-identical community for both bacteria and phytoplankton at all stations. This is despite differences in the protocol such as volume filtered and temporal resolution, aligning with prior studies, which have shown similar results 42,43 . A recent study performed using the 3G ESP also demonstrated that results were equivalent between autonomous and manual sampling 44 .…”
Section: Discussionsupporting
confidence: 89%
“…By collectively analyzing the concentrations of tetA , ermB , qnrS and bla CTX-M obtained from AWW2 to AWW4, EP1, EP2 and EP5 using 0.2/0.5 mL sample volume with no pre-spin step yielded significantly greater ARG concentrations than in EP3 and EP9 using 1.0 mL and EP6 using 0.5 mL sample volume. The superior performance of small sample volumes for nucleic acid extraction has also been observed in previous studies [ 7 , 22 , 28 ]. On the one hand, employing small sample volume may minimize the interference of toilet paper during the extraction process, which may introduce PCR inhibitors and compromise amplification efficiency [ 11 ].…”
Section: Discussionsupporting
confidence: 76%
“…Ideally, researchers should aim to collect enough cells so that amplification is not necessary. In these cases, DNA can be extracted with low biomass-input methods (Bramucci et al 2021 ). When this is not possible, a potential alternative to MDA is primary template-directed amplification (PTA) (Gonzalez-Pena et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%